What works and what's just? - McNeill, Fergus (2009)
This paper is based on a presentation entitled 'What Works in Probation', delivered to an Invitational Conference for Directors of Probation Services in Europe organised by the Council of Europe, the Conference Permanente Européenne de la Probation and the French Ministry of Justice at the Palais de l'Europe in Strasbourg (26th-28th November, 2008). Drawing on a much more extensive and separately published report about the effectiveness of offender supervision (McNeill, 2009), I try to argue here that, despite the apparently technical nature of questions of effectiveness, in fact any considered and critical analysis of the empirical evidence about desistance, rehabilitation and' what works?' compel us to consider the moral character and context of criminal justice interventions